LudosTop: estratégia de jogos e realidade virtual com vistas ao desenvolvimento do pensamento lógico-matemático - Freitas, Marlene Roque de (2008)
The objective of this work is to investigate the use of computacional techniques that, associated to Virtual Reality, make possible the creation of an educational software. The idea is that this software were based on cognitive and entertaining techniques so that it could aid the educator's activity. Such learning atmosphere is concerning mathematical contents and its public are students of the Fundamental Teaching (2nd and 3rd series). The pedagogic base for its elaboration is the Jean Piaget's theory of the intellectual development. It involves game strategies, attributing entertaining characteristics to the learning moments. For that reason, in fact, was denominated Ludostop. Such a funny feature is coherent, for its time, with the characteristics of the age group in subject. The work includes the analysis of some educational softwares, and it concerns to the area of Mathematics; such programs served as theoretical and methodological referencial for the elaboration of the proposed software. The design of the software is based on the image of a spaceship, ready for an interplanetary trip. Inside the ship, the user has the possibility to access a Laptop. The Laptop makes available a game ( Quarto ), and it also allows to access links that bring information about mathematics to scientists. The objective of the game is to align geometric solids with common attributes. From the pedagogic point of view, the identification of such attributes stimulates the development of the mathematical logical reasoning, as it is explained in the theoretical base (Chapter 2). The work includes, also, description of Virtual Reality techniques and of the programming languages (VRML and JavaScript) used. Besides, the work presents details of the system implementation. The software was tested in children of the Fundamental Teaching, generating, finally, a report about this experience.